2007
DOI: 10.1021/om070080g
|View full text |Cite
|
Sign up to set email alerts
|

1,4-Dihydro-1,4-diarsinine:  Facile Synthesis via Nonvolatile Arsenic Intermediates by Radical Reactions

Abstract: dro-1,4-diarsinines, were synthesized by radical reactions of pentamethylcyclopentaarsine ( 1) and acetylenic compounds. The radical reactions of 1 and acetylenic compounds such as dimethyl acetylenedicarboxylate (2a) and 4-ethynylpyridine (2b) in refluxing benzene with 2,2′-azobis(isobutyronitrile) (AIBN; 5 mol %) under a nitrogen atmosphere proVided the corresponding 1,4-dihydro-1,4-diarsinines (3). Formation of 1,4dihydro-1,4-diarsinine was confirmed by 1 H and 13 C NMR spectra and FAB-mass spectrometry. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 13 publications
0
18
0
1
Order By: Relevance
“…• from that in trans-DHDAtBu of 101.05 (10) • . The extension of the interior angles at around the coordinated arsenic atoms might be due to reduce electron density of the paired electrons on the arsenic atoms by the coordination which reduces the repulsion between the paired and unpaired electrons on the arsenic atoms.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…• from that in trans-DHDAtBu of 101.05 (10) • . The extension of the interior angles at around the coordinated arsenic atoms might be due to reduce electron density of the paired electrons on the arsenic atoms by the coordination which reduces the repulsion between the paired and unpaired electrons on the arsenic atoms.…”
Section: Methodsmentioning
confidence: 92%
“…We have synthesized 1,4-dihydro-1,4-diarsinines, 1,4-diarsa-1,4-cyclohexadienes, as cyclic ditopic organoarsenic ligands by radical reaction of pentamethylcyclopentaarsine (cyclo-(MeAs) 5 ) and acetylene derivatives [10,11]. The 1,4-dihydro-1,4-diarsinines are stable toward air and moisture.…”
Section: Introductionmentioning
confidence: 99%
“…and methyl moieties confirmed the polyimide structure. Analysis of PI-1 by 13 C-NMR spectroscopy in DMSO-d 6 showed only one sharp resonance for the methyl carbon at 10.8 p.p.m., suggesting that the arsenic in the polymer existed in a pure form and no oxidized arsenic was present (Figure 3b). The polyimide showed a 10% weight loss at 329 1C under air.…”
Section: Polymerizationmentioning
confidence: 99%
“…We previously reported the facile synthesis of a novel cis-1,4-diarsa-2,5-cyclohexadiene, that is, cis-1,4-dihydro-1,4-dimethyl-2,3,5,6-tetrakis(t-butoxycarbonyl)-1,4-diarsinine (cis-DHDAtBu), which was synthesized by the radical reaction of pentamethylcyclopentaarsine (cyclo-(MeAs) 5 ) and di-t-butyl acetylenedicarboxylate. 13,14 Their stability against air and moisture was high enough to allow handling in air. In this study, we found that cis-1,4-dihydro-1,4-dimethyl-1,4-diarsinine-2,3,5,6-tetracarboxylic acid dianhydride (cis-DHDADA) was quantitatively formed from cis-DHDAtBu treated with formic acid as a Brønsted acid.…”
Section: Introductionmentioning
confidence: 99%
“…During the RCRAC process, the vinyl radical can be stabilized by electron‐withdrawing substituents, such as esters, resulting in isomerization from the Z form to the E form . Dimerization of the E ‐form vinyl radical species produces cyclic diarsenic compounds, cis ‐DHDAs ( 32 ).…”
Section: Conjugated Polymersmentioning
confidence: 99%